TATA KELOLA TERMINAL BANDAR RAYA PAYUNG SEKAKI KOTA PEKANBARU TAHUN 2018 - Wita. S; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Bandar Raya Payung Sekaki Terminal is a public transport terminal that functions as a road transportation infrastructure for the purpose of loading and unloading people and / or goods as well as regulating the arrival and departure of public vehicles, which is a manifestation of a transportation network node that in its management and implementation functions is given guidance and supervision of the Department of Transportation. The purpose of this study was to determine the governance of the Bandar Raya Payung Sekaki terminal at Pekanbaru City and to find out what factors are hampering the management of the Bandar Raya Payung Sekaki terminal at Pekanbaru City. This research was conducted at the Bandar Raya Payung Sekaki Terminal in Pekanbaru City. The informants in this study are parties related to this research.From the results of this study it can be concluded that the Management of Payung Sekaki Bandaraya Terminal by BPTD (Land Transportation Management Center) IV Riau Kepri has not been implemented optimally. From the results of interviews and observations, it was found that many of the activities carried out were not in accordance with the planned targets. If seen from the development of the Bandar Raya Payung Sekaki terminal, no satisfactory results have been seen that can overcome traffic problems in the city of Pekanbaru. This is because the management of the terminal manager in the supervision process in the activities carried out does not do routinely, so that each PO is still operating based on their own concept. The quiet of the terminal also makes many of the facilities available in the terminal neglected, such as counters that are still empty, stalls that have not been rented, lodging that is rarely used and also other facilities in the management of the terminal still get treatment. From the findings in the field there are several factors that hamper the management of the Bandar Raya Payung Sekaki Pekanbaru City terminal, namely human resources, and the lack of facilities and infrastructure owned by the terminal to assist in the terminal management process, this will certainly lead to ineffective terminal management processes. Keywords: Governance, Bandar Raya Payung Sekaki Terminal